(untitled) (Psychology Travelogs, 2025)
The article examines the current challenges that impede the effective implementation of state programs for the social and psychological adaptation of severely wounded persons in the context of full-scale armed aggression against Ukraine. The current state, regional and local initiatives to provide social and psychological assistance in Ukraine in 2023-2025 are analyzed. It is revealed that despite the positive developments in the formation of programs, including the creation of mobile multidisciplinary teams, art therapy centers and a system of veteran assistants, the effectiveness of implementation remains limited due to a number of challenges. The main challenges that impede the effective implementation of programs for the social and psychological adaptation of severely wounded persons in Ukraine are considered, taking into account administrative, personnel, territorial, socio-cultural and communication factors. It is noted that despite the positive trend towards expanding the formats of assistance, there are a number of deep-rooted systemic barriers that significantly reduce the effectiveness of these measures. Strategic ways to overcome the identified challenges that impede the effective implementation of programs for the social and psychological adaptation of severely wounded are proposed. The importance of comprehensive development of institutional infrastructure to ensure sustainable and effective implementation of support programs is emphasized. Particular attention is paid to the training of qualified professionals capable of dealing with the consequences of the traumatic experience of veterans and war victims. The results of the study can be useful for social policy makers, practical psychologists, social workers, representatives of NGOs and researchers working in the field of rehabilitation of veterans and war victims.